ANALISIS KLORIN PADA BERAS DI PASAR INDUK JAKABARING DAN SUMBANGSIHNYA TERHADAP MATA PELAJARAN BIOLOGI PADA MATERI MAKANAN BERGIZI DAN MENU SEIMBANG DI KELAS XI SMA/MA - Yulia Tri Samiha; Syarifah Syarifah; Dwi Astria Elmiana (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2016)
Rice is a staple food that easily processed easy to prepare, delicious and contains carbohydrate and protein as energy sources. Chlorine is not permitted to be used for rice because it can harm the respiratory system and the liquid can damage humans skin. The Health Ministry of Indonesian Republic already ruled about Ingredient Added Food (IAF) in rule No.722/Menkes/Per/IX/88, it said that Chlorine forbidden to used for rice because Chlorine is not the list of IAF as whitening and cooking wheat group. The purpose of this research is identify and count how much Chlorine in branded rice and inbranded rice that sold in Center Market of Jakabaring Palembang. There are 14 samples of rice in consist of 7 branded rice samples and 7 inbranded rice samples that took from 4 shops and 3 rice sell distributor in Center Market of Jakabaring Palembang. This research was done on 18- August 2015 at Chemical Laboratory of UIN Raden Fatah Palembang. Chlorine was tested by using Colour Reaction Method, Iodometry Titration Method and Organoleptic Test to identify rice physic that contain Chlorine. The result of this research showed that all samples are negative Chlorine. Based on Organoleptic Test, the sampel without Chlorine has characteristic in pure white colour, no medicine smell, not slippery and unfragile, meanwhile from the positive control that analized contain Chlorine 3,99 mg, showed that rice with Chlorine has characteristic more shine untransparant white colour, has medicine smell, slippery and fragile. In this regard it can be concluded that all sample are not contained Chlorine and save to consumed. This research after to be appropriate to the syllabus concept of K13 it can be as gift as education sector of Biology Education Subject in form Studying Execution Planning (RPP), Student Work Sheet (LKS) were have done validated by 2 validators and the result is valid, and in form Student Studying Video, too.